Effects of Integrated Soil Fertility Management Technologies on the Productivity of Sorghum in the Drier Parts of Upper Eastern Kenya - Hezron Mogaka; Shadrack Kiprotich (Journal of Global Innovations in Agricultural Sciences)
Declining soil fertility amid the devastating effects of climate change is a threat to the state of food security in developing countries like Kenya. Enhancing production intervention through sustainable farming practices like integrated soil fertility management (ISFM) technologies has been promoted. However, there is a dearth of knowledge revealing the efficacy of such technologies, especially in dry regions of the country. Therefore, this study evaluated the effect of integrated soil fertility management technologies on sorghum productivity in the drier parts of Upper Eastern Kenya. Data was collected from 370 sorghum farmers using a semi-structured questionnaire. The data was analyzed using descriptive statistics (percentages) and Propensity Score Matching (PSM). The initial PSM stage revealed that various socioeconomic and institutional aspects (subsistence farming, access to extension services, perception of innovations, road infrastructure, ISFM awareness and ISFM costs) influence the adoption decision of ISFM. Further, the findings reveal that farmers who adopted ISFM technologies recorded increased sorghum productivity. Hence, the productivity of adopters was better than that of non-adopters. Improving adoption, therefore requires the facilitation of agricultural institutions and service providers who are key in imparting vital knowledge and creating awareness of productive technologies such as ISFM. Similarly, the results have wider policy effects for agriculture, especially in places where ISFM may be very important for long-term food security and agricultural productivity.